Improving Farmer Willingness to Participate in the Transfer of Land Rights in Rural China: A Preference-Based Income Distribution Scheme - Lei Yan; Xubin Lei; Kairong Hong; Hui Li; Mengyuan Chen (Land, 2022)
Promoting the transfer of rural land is an important way for many developing countries to improve the efficiency of rural land use and develop the rural economy. A reasonable income distribution scheme (IDS) is the key to enhancing farmer willingness to participate in the transfer of rural construction land use rights. However, little attention has been paid to farmers’ preference for the IDS of the transfer of rural collective construction land use rights. This research aims to detect the farmers’ preference for IDS in the process of rural collective land rights transfer. Based on the survey data of 489 farmers in Liuyang City, Hunan Province and Deqing County, Zhejiang Province, China, a random parameter Logit model is used to explore their preference for the IDS of the transfer of rural collective construction land use rights. The results show that, in general, the farmers focus on the income distribution ratio and pension in the IDS, which will significantly improve their utility. There are obvious regional differences in their preference for IDSs. For example, farmers in Liuyang prefer payment in shares, while those in Deqing prefer cash. Thus, the IDS for the transfer of rural collective construction land use rights should be based on the basic principle of ensuring fair land value-added income for the farmers, increased payment forms with social security functions, and reasonable IDSs in accord with the preferences of farmers in different regions, so as to enhance farmer willingness to participate.